2013
DOI: 10.3923/pjbs.2013.431.434
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effect of Epiphytic Bacteria from Marine Algae, Southeastern India

Abstract: Aim of this study was to evaluate the antagonistic potential of epibiotic bacteria from seaweeds, Ulva lactuca, Dictyota dichotoma and Padina tetrastromatica against some potent human pathogens. The epibiotic bacteria of Ulva lactuca shows higher level of inhibition properties than the other species. The strain UL1 shows broad spectrum inhibitory activity against 7 pathogens. The inhibitory level of epibiotic bacteria ranged from low to moderate activity. The present investigation suggests that the epibiotic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Microorganisms will automatically acquire there resistance towards common antibiotics by altering their metabolism and genetic structure. These microbial compounds are most prominent source for discover and production for new drugs (Zhang et al, 2009;Yuan et al, 2010;Chellaram et al, 2013). This study showed that the isolated bacterium Bacillus kochii has excellent herbicidal activity.…”
Section: Discussionmentioning
confidence: 93%
“…Microorganisms will automatically acquire there resistance towards common antibiotics by altering their metabolism and genetic structure. These microbial compounds are most prominent source for discover and production for new drugs (Zhang et al, 2009;Yuan et al, 2010;Chellaram et al, 2013). This study showed that the isolated bacterium Bacillus kochii has excellent herbicidal activity.…”
Section: Discussionmentioning
confidence: 93%
“…Secondary metabolites are increasingly recognized for their importance for industrial and medical applications (Faulkner, 2000 ; Kelecom, 2002 ). Various novel compounds with antibiotic activity have already been identified from seaweed-associated bacteria (Chellaram et al, 2013 ; Horta et al, 2014 ; Martin et al, 2014 ). Several species of marine bacteria have been isolated from brown algae such as the spot-wounded fronds of Laminaria japonica (Sawabe et al, 2000 ), the surface of Fucus serratus (Johansen et al, 1999 ) and from rotten thallus of Fucus evanescens (Ivanova et al, 2004 ) and Undaria pinnatifida (Lee et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds of the genus Padina were previously reported to harbor epiphytic bacteria with variety of biological activities such as antibacterial activities of epiphytic bacteria isolated from P. arborescens , which was collected from Awaji Island, Japan (Kanagasabhapathy et al, 2006 ). Bacterial isolates from a close relative of P. pavonica, P. tetrastromatica collected from southeastern India were previously studied for their antibacterial activities against a panel of human pathogens (Chellaram et al, 2013 ; Ravisankar et al, 2013 ). However, since the geographic location is amongst the factors that impact on a bacterial community's diversity, composition and secondary metabolites production, the study of the epiphytic bacteria of P. pavonica , which is abundant at the Tunisian coast, was considered to be promising for finding novel antibacterial compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Several anti-inflammatory, digestive, anti-necrotic, neuroprotective and hepatoprotective drugs have recently been shown to have an antioxidant or anti-radical scavenging mechanism as part of their activity [6].…”
Section: Introductionmentioning
confidence: 99%